Penerapan ELPSA Framework Berbantuan Game pada Materi Eksponensial - Putri, Devi Arhami; Johar, Rahmah; Hasbi, Muhammad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
<span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">The Application of the ELPSA Framework Assisted by Game in Teaching Exponential<span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">. <span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">There is still a tendency for students to avoid mathematical assignments is a challenge for educators. Therefore, to present interesting and quality mathematics learning, one of them can be through the ELPSA framework. ELPSA framework is a mathematical learning approach that contains five components, namely experience, language, pictorial, symbolic, and application. The game was chosen to present training as a part of symbolic component that attract students. This study aims to determine the mastery of student learning through the application of the ELPSA framework assisted by games on exponential material, student responses to the learning activity, and the dynamics of students’ emotional activity in game utilization. <span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This <span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">research use mixed method with convergent parallel mixed method design. The instruments used were learning outcomes tests, student response questionnaires, and observation sheets of student emotional activity. The study population was all students of MTsN 1 Aceh Tengah, and the sample was 17 students of class VIII-1. Based on the results of data processing using the t test, it can be concluded that the value of students reaches completeness. In addition, students respond well to learning and the use of games. Observation of the emotional activity of students during play shows the seriousness is dominating the emotional activity that arises, followed by pleasure, and curiosity. Whereas signs of boredom and disappointment do not arise. This study presents alternative mathematical learning designs to achieve learning goals, as well as attracting students.